Conceptual and Practical Problems of Moral Enhancement. (24th March 2014) - Beck, Birgit
Abstract Recently, the debate on human enhancement has shifted from familiar topics like cognitive enhancement and mood enhancement to a new and – to no one's surprise – controversial subject, namely moral enhancement. Some proponents from the transhumanist camp allude to the 'urgent need' of improving the moral conduct of humankind in the face of ever growing technological progress and the substantial dangers entailed in this enterprise. Other thinkers express more sceptical views about this proposal. As the debate has revealed so far, there is no shared opinion among philosophers (or scientists) about the meaning, prospects, and ethical evaluation of moral enhancement. In this article I will address several conceptual and practical problems of this issue, in order to encourage discussion about the prospects of (thinking about) moral enhancement in the future. My assumption is that (i) for the short term, there is little chance of arriving at an agreement on the proper understanding of morality and the appropriateness of one single (meta‐)ethical theory; (ii) apart from this, there are further philosophical puzzles loosely referred to in the debate which add to theoretical confusion; and (iii) even if these conceptual problems could be solved, there are still practical problems to be smoothed out if moral enhancement is ever to gain relevance apart from merely theoretical interest. My tentative conclusion, therefore, will be that moral enhancement is not very likely to be made sense of – let alone realized – in the medium‐term future.